Penerapan Sistem Informasi Batik Solo Trans Berbasis Website dengan Metode Prototype Guna Mendukung Sektor Pariwisata Kota Solo - Hidayati, Anindya Nurindah; Sutopo, Joko (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The city of Solo or commonly dubbed as “Solo The Spirit of Java” is a city famous for its tourism and cultural sectors. The lack of information about Batik Solo Trans public transportation is one of the obstacles to mobility in Solo, including mobility in the tourism sector. With the lack of information about Batik Solo Trans Public Transportation, it gave birth to an idea to develop a website designed to provide information about Batik Solo Trans Public Transportation. The information contained is about route details, operational hours of Batik Solo Trans public transportation, and the cost required to use Batik Solo Trans public transportation. The Website-Based Batik Solo Trans Public Transportation Service System with the Prototype Method is specifically designed to help passengers to use public transportation more easily and get to their destination smoothly using Batik Solo Trans Public Transportation. With this website, access to Batik Solo Trans becomes easier, and is expected to increase mobility in Solo City, especially in the tourism sector.